Decoding dynamic faces and scenes without awareness under dis-continuous flash suppression - Yen-Ju Feng; Shao-Min Hung; Po-Jang Hsieh (Communications Biology)
Abstract In the perceptual sciences, there is an ongoing debate about the depth of unconscious processing. Here, we address this issue by implementing three improvements with regards to paradigm, stimuli and analyses to explore the neural correlates of unconscious face processing. Our results demonstrated that conscious faces elicited broader univariate activations than conscious scenes. Such results were absent when faces/scenes were suppressed and invisible (n = 43). However, further whole-brain multivariate classification revealed that both static and dynamic invisible faces could be distinguished from scenes in the occipital-temporal region. ROI analysis showed that bilateral FFA and OFA could differentiate dynamic invisible faces from dynamic invisible scenes. These findings suggest that interocularly suppressed faces are still processed in-depth in the ventral visual stream. Therefore, our study highlights the importance of optimizing stimulus signal, experimental paradigm, and analysis to extract unconscious signals in the brain.